Foxn1-β5t transcriptional axis controls CD8+ T-cell production in the thymus - Muhammad Myn Uddin (Nature Portfolio, 2017)
Foxn1 is involved in thymic epithelial cell (TEC) and CD8+T cell development. Here the authors show this development requires Foxn1 binding proximal to, and inducing transcription of, the gene encoding β5t in cortical TECs.